2015
DOI: 10.1039/c4an01856g
|View full text |Cite
|
Sign up to set email alerts
|

Raman microspectroscopy of human aortic valves: investigation of the local and global biochemical changes associated with calcification in aortic stenosis

Abstract: Raman microspectroscopy was applied to characterize the local and global biochemical changes associated with calcification in human stenotic aortic valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
(66 reference statements)
2
16
0
Order By: Relevance
“…Glucose supplementation in the in OSM medium, even in the high concentration (4.5 g/L), did not cause significant changes. Nevertheless, the calcification in the form of inorganic phosphate salt deposits that were found in aortic valve tissue was not observed in HAVICs in in vitro cell culture upon incubation with OSM and OSM/glucose for 7 days. Previous studies highlight the extracellular origin of calcification process during which nucleation of calcium nodules takes place in ECM rich in type I collagen and fibronectin .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Glucose supplementation in the in OSM medium, even in the high concentration (4.5 g/L), did not cause significant changes. Nevertheless, the calcification in the form of inorganic phosphate salt deposits that were found in aortic valve tissue was not observed in HAVICs in in vitro cell culture upon incubation with OSM and OSM/glucose for 7 days. Previous studies highlight the extracellular origin of calcification process during which nucleation of calcium nodules takes place in ECM rich in type I collagen and fibronectin .…”
Section: Resultsmentioning
confidence: 89%
“…Its effect was also tested on vascular SMCs, proving the induction of osteogenic morphology, physiology, and gene expression, which may be a contributing factor to the formation of calcifying vascular cells . Moreover, we have previously found that lipid deposits accompany calcification in the tissue of stenotic aortic valves …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations